Effects of fermented wheat bran and yeast culture on growth performance, immunity, and intestinal microflora in growing-finishing pigs. (23rd October 2021) - He, Wei; Gao, Yanan; Guo, Zhiqiang; Yang, Zheng; Wang, Xiaoxu; Liu, Honggui; Sun, Haoyang; Shi, Baoming
Abstract: This study was conducted to evaluate the effects of feeding fermented wheat bran (FWB ) and yeast culture (YC ) on growth performance, immune levels, and intestinal microflora in growing-finishing pigs. In total, 96 crossbred pigs were randomly distributed into four treatments with four replicates pens and six pigs per pen. This study was performed using a 2 × 2 factor design: 1) CON (basal diet), 2) FWB (basal diet + 5% FWB), 3) YC (basal diet + 2% YC), and 4) FWB + YC (basal diet + 5% FWB + 2% YC). Dietary FWB supplementation significantly increased the average daily gain and significantly decreased the feed gain ratio of growing-finishing pigs ( P < 0.05). Supplementation of FWB and YC improved the immune capacity and reduced the inflammation level of growing-finishing pigs ( P < 0.05). In addition, pigs fed FWB, YC, and FWB + YC diets showed better intestinal development and morphology compared with those CON pigs. The relative abundance of Streptococcus in the FWB group was significantly lower than that in the CON group ( P < 0.05), and the relative abundance of probiotics ( unclassified_f_Lachnospiraceae, Turicibacter ) increased significantly ( P < 0.05). Furthermore, the relative abundance of probiotics ( Lactobacillus, norank_f_Muribaculaceae ) in the YC group was significantly increased compared with the CON group ( P < 0.05). The results of this study observed positive effects of FWB and YC on growing-finishing pigs, which provides insights into the application of biological feed in swine industry.